Experience of mothers with perinatal depression: a scoping review - Christiana, Indah; Widiyastuti, Nurul Eko; Kusumawati, Diana (Universitas Aisyiyah Yogyakarta, 2025)
The perinatal period brings physical, emotional, and social changes for mothers, which heighten their risk of experiencing perinatal depression. In 2022, its prevalence reached 20% in low- to middle-income countries. Worldwide, postpartum depression is regarded as a significant public health issue that demands targeted interventions. This study aims to review the results of research on the mothers’ experiences with perinatal depression. It used scoping review that consisted stages of conducting a focusing review using the SPIDER framework (Sample size, Phenomenon of Interest, Study Design, Evaluation, and Research type); conducting literature searches using relevant databases, i.e., Pubmed, Wiley, ScienceDirect, ProQuest, Lexis Nexis and Sage Journals; Relevant studies were selected based on inclusion and exclusion criteria; conducting JBI critical appraisal to assess the quality of the literature; and conducting data extraction, analyzing and reporting the results. The PRISMA Flowchart, representing the Preferred Reporting Items for Systematic Reviews and Meta-Analyses, was utilized to formally delineate the process of the literature search. Twenty articles met the inclusion criteria and were included in the review. Through thematic analysis, key concepts were identified and organized into three themes: symptoms, causes, and treatment of perinatal depression. Perinatal depression is a significant condition that requires timely detection and appropriate treatment to safeguard the health of both mothers and their babies. This study highlights how maternal experiences influence mental health and recovery, and it supports the development of interventions that are more sensitive to emotional and cultural needs.